2012
DOI: 10.4236/ojped.2012.22019
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of adverse drug reactions in children in five Italian paediatric wards

Abstract: Adverse drug reactions (ADRs) are an important clinical problem and contribute significantly to mortality and morbidity. Scant data on the safety of drug use in children are usually available at the time of marketing authorization, due to the limited number of trials performed in the paediatric population. Few studies monitored the incidence of ADRs in Italian hospitalized children, that cannot be compared for methodological reasons. A 6-month prospective observational study was, therefore, conducted on the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…In the general child population, as documented by other studies, the largest share of ADR SOCs reported was Skin Appendage Disorders (60.1%) ( Morales-Olivas et al, 2000 ; Clavenna and Bonati, 2009 ; Star et al, 2011 ; Gallo et al, 2012 ; Rashed et al, 2012a ). A study by Star et al (2011) found that ADRs related to skin reactions were more frequently seen in children than in adults.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the general child population, as documented by other studies, the largest share of ADR SOCs reported was Skin Appendage Disorders (60.1%) ( Morales-Olivas et al, 2000 ; Clavenna and Bonati, 2009 ; Star et al, 2011 ; Gallo et al, 2012 ; Rashed et al, 2012a ). A study by Star et al (2011) found that ADRs related to skin reactions were more frequently seen in children than in adults.…”
Section: Discussionsupporting
confidence: 63%
“…In a multicenter prospective cohort study of hospitalized children involving five countries, including Malaysia, similar findings were observed by Rashed et al (2012a) . A huge number of Antibacterials for Systemic Use were prescribed in the general pediatric population and a higher number of ADRs were reported for agents from this therapeutic group ( Clavenna and Bonati, 2009 ; Priyadharsini et al, 2011 ; Barzaga Arencibia et al, 2012 ; Gallo et al, 2012 ; Rashed et al, 2012a ). Due to the issue of antibiotic resistance, often multiple types of antibiotics and broad spectrum antibiotics at high doses were used for neonatal infection ( Manan et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ADRs this study found a higher incidence of ADRs (3.8 per 100 admissions) than the studies done in Italy, 0.9 % [ 29 ] and France, 2.64 % [ 30 ]; and a lower incidence than the studies done in Germany, 31.8 % [ 31 ], Saudi Arabia, 8.2 % [ 32 ] and Brazil, 12.5 % [ 33 ]. The possible reasons for the differences might be due to differences in the length of hospital stay of patients and also methods used to detect events.…”
Section: Discussionmentioning
confidence: 47%
“…It must also be recognized that systems designed to detect ADRs in other settings may not be ideally suited for implementation in this specific outpatient environment. As an example, although the presence of dedicated ADR personnel (supplemental to the existing pharmacy teams) can increase the detection of ADRs, 17,18,44 adoption of a single point of contact for incident reporting does not appear to be strongly supported by the outpatient pharmacists surveyed in this study, many of whom clearly felt compelled, professionally, to exercise a leading role in this area. Instead, given the encouraging improvements reported here (following an extremely low-intensity educational intervention), more formalized training interventions should be investigated preferentially for pharmacists in these practice sites.…”
Section: Discussionmentioning
confidence: 78%